Contemporary Jurisprudence and Legal Abortion in Asian Muslim Countries: The Politics of Global Abortion Rights - Tayebi, Naeimeh; Radmehr, Zohreh; Ghodrati, Fatemeh (Current Women's Health Reviews, 2025)
BackgroundReligion plays an important role in a patient's decision to have an abortion, as well as in a country's abortion policy. However, a holistic understanding of the position of Asian Islamic countries has been less researched.ObjectiveContemporary jurisprudence and legal abortion in Asian Muslim countries; The politics of global abortion rights.MethodsThe article examined jurisprudence and legal issues of abortion in 12 Asian Muslim countries between 1990 and 2021, searching in reliable databases using the keywords of “abortion, civil law, criminal consequences.” The exclusion criteria were inadequate data in the study, editorial studies, and case reports.ResultsAbortion at the mother's request is legal in Turkey, Tajikistan, Kyrgyzstan, Turkmenistan and the Republic of Azerbaijan. In Iran, Malaysia, Afghanistan, Brunei and Indonesia, abortion is forbidden at any stage of gestation but before 4 months (Iran) and up to 22 weeks (Malaysia). In Brunei and Indonesia, it is permitted if a mother’s life is in danger. Abortion is legal in Bangladesh under the heading of “menstrual regulation,” but a mother's request for abortion is illegal unless the mother's life is in danger. Termination of pregnancy is a crime and punishable in Pakistan unless it is done in good faith or to preserve the woman's life through “necessary treatment.”ConclusionThe diversity of procedures in Asian Muslim countries depends on their legal system, whether it is exclusively based on Sharia law (Iran), a combination of Sharia law along with civil law (Saudi Arabia), or whether the legal system is not officially based on Sharia laws (Turkey).
Keywords: Laws